Cover Feature: Deciphering the Role of Noncovalent Interactions in the Conformations of Dibenzo‐1, 5‐dichalcogenocines (ChemPlusChem 4/2022). Issue 4 (25th February 2022) - Weiss, Robin; Cornaton, Yann; Khartabil, Hassan; Groslambert, Loïc; Hénon, Eric; Pale, Patrick; Djukic, Jean‐Pierre; Mamane, Victor
Abstract : The Cover Feature illustrates the pathways undergone by ditellurocines from the solid state (represented by stones) to the solution (represented by the water cascade). Once the ditellurocine crystals/stones roll down in the cascade, metamorphosis occurs, from the cubic‐like arrangement to a caterpillar (less stable chair conformation) then to a lying butterfly (transition state) and to a flying butterfly (more stable boat conformation). More information can be found in the Full Paper by J.‐P. Djukic, V. Mamane, and co‐workers .